2015
DOI: 10.1080/21513732.2015.1071282
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of on-farm cassava biodiversity in Ogun State, Nigeria

Abstract: Global food security depends on agro-biodiversity. However, an enormous quantum of genetic diversity of agricultural crops has been lost over the last century, and this implies vulnerability, increased economic risks, reduced food security, loss of resources for future adaptation as well as reduced and unsustainable agricultural growth opportunities. This study examined the determinants of on-farm cassava biodiversity in Ogun State, Nigeria. We profiled cassava biodiversity indices of farmers in the state acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
4
6
0
Order By: Relevance
“…The mean household size of the respondents was about six persons. This is in line with the findings of [34], where the average household size for a cassava farmer in Ogun State is seven. Most (83.3%) of the respondents owned their processing centres and over half (57.0%) had used their own funds to establish their enterprises.…”
Section: Summary Of Description Of Cassava Processorssupporting
confidence: 92%
See 1 more Smart Citation
“…The mean household size of the respondents was about six persons. This is in line with the findings of [34], where the average household size for a cassava farmer in Ogun State is seven. Most (83.3%) of the respondents owned their processing centres and over half (57.0%) had used their own funds to establish their enterprises.…”
Section: Summary Of Description Of Cassava Processorssupporting
confidence: 92%
“…More than half of the processors fell within the age range of 46 to 65 years. The mean age of the respondents in the study was 48 years, which is similar to the mean age of cassava processors found by [34] in Ogun State. This shows that the majority of the respondents were of an active working age and may appreciate the opportunity to use value-added solid-waste management.…”
Section: Estimation Methodssupporting
confidence: 81%
“…The inverse relationship between age and adoption in the eastern region can be attributed to the fact that older farmers are used to their conventional ways of farming and might be reluctant to make such a switch, unlike young people who are associated with a higher risk-taking behavior and possibly more open to the use of newer technologies than their parents. Inconsistent with the findings of Da Encarnação and Zwane (2020), Danso-Abbeam et al 2017 and Obayelu et al (2015), thier studies have reported that the older the farmer the more likely to adopt improved varieties. Filho et al (2011) also disagreed and attested that, despite the fact that aged farmers have challenges to the access information on new technologies, they are fast to adopt new innovation, because they are more likely to assign substantial resources to its acquisition than the youths.…”
Section: Agementioning
confidence: 67%
“…Several contributions of this issue address biodiversity conservation in agricultural systems. Obayelu et al (2015) provide a case for cassava farming practices in Nigeria. They provide a model that explains the diversity of cassava varieties.…”
Section: This Issuementioning
confidence: 99%